Some remarks about "atimía" - García Domingo, Enrique (Cuadernos de Filología Clásica. Estudios griegos e indoeuropeos, 2015)
The main purpose of this study is to demonstrate these points: a) a prosecutor that did not get a fi fth of the votes in a public lawsuit or did not continue an initiated action immediately incurred a fi ne of 1.000 drachmas inexorably linked to partial and temporary (not permanent) atimia. If, as later, he did not settle the debt in the ninth pritany, it was doubled (2.000 drachmas) and atimia went from partial to total. As he paid off, he became epitimos; b) a prosecutor who did not go on with an eisangelia was subject to the preceding punishment; however a plaintiff who did not obtain a fi fth of the votes in it did not suffer any punishment at fi rst, but from about 331 BC he was punished with 1.000 drachmas, but not with partial atimia; c) the defendant who was sentenced on euthynai, on some graphai or dikai to indemnify the state or fi ned by a magistrate, turned into public debtor from that very moment, but not into atimos. If, as a last resort, he did not pay off the debt in the ninth prytany, it was doubled and he became fully atimos. He was again epitimos as soon as he cleared off what he owed.
Keywords: atimia; atimos; debt; public debtor; endeixis; epitimos; fine; prytany.